New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera - Gumovsky, Alex (Zootaxa, 2018)
Three new species groups and seven species of the genus Pediobius Walker are described from the Afrotropical realm: the marjoriae group, with P. marjoriae Kerrich (described from Uganda), P. rohombaya Gumovsky sp. n. (from the Central African Republic (CAR), the Democratic Republic of the Congo (DRC), Gabon, Uganda) and P. orungu Gumovsky sp. n. (from Gabon); the afroteres group with P. afroteres Gumovsky sp. n. (from South Africa, Zimbabwe, Malawi, Kenya, Uganda, DRC, Cameroon) and P. kafroteres Gumovsky sp. n. (from Cameroon); the askari group with P. askari Gumovsky sp. n. (from South Africa, Zimbabwe, Kenya, Tanzania, DRC, Ivory Coast) and P. maleficus Gumovsky sp. n. (from Kenya, DRC, CAR, Cameroon, Gabon); and P. nganga Gumovsky sp. n. (from DRC) (not assigned to any group). All these species are characterized by the relatively wide and robust head with elongate and/or narrowed lower face and the antennae attached near or below the lower eye margins. Morphological features of the species, as well as their habitat distribution, are discussed. The comparison of the new species with similar taxa of Entedoninae suggested the following synonymies: Rhynchentedon Girault and Pediobomyia Girault under Pediobius (syn. n.); Bomyiabius frontus Narendran, Pediobomyia budaicus Narendran and Pediobomyia lankicus Narendran under Pediobomyia darwini Girault (syn. n.). The following new combinations are proposed: Pediobius maximus (Girault), P. achterbergi (Gumovsky), P. narendrani (Gumovsky), P. brevicaulis (Hansson), P. canaliculatus (Hansson) and P. darwini (Girault) (comb. n.). Ant parasitoids P. marjoriae and Myrmokata diparoides Bouček are recorded from DRC for the first time.